Large mammal species richness and late Quaternary precipitation change in south‐western Australia. (29th July 2016) - Faith, J. Tyler; Dortch, Joe; Jones, Chelsea; Shulmeister, James; Travouillon, Kenny J.
ABSTRACT: The precipitation history of south‐west Australia since the Last Glacial Maximum (LGM) has important implications for understanding southern hemisphere climate dynamics. Previously reported environmental records indicating more open vegetation during the LGM have been interpreted in terms of aridity, but such changes can be explained by alternative mechanisms. To provide new evidence concerning the region's Quaternary precipitation history, we examine temporal changes in large mammal richness at four south‐west Australian fossil sites: Devil's Lair, Tunnel Cave, Witchcliffe Rock Shelter and Rainbow Cave. Large mammal richness is correlated strongly with mean annual precipitation across 53 modern Australian communities. Extending this relationship to the fossil record, a steady increase in richness from the LGM to the onset of the Holocene at both Devil's Lair and Tunnel Cave is consistent with increased precipitation through time. This supports previous interpretations of a more arid LGM and implies regional heterogeneity in the position of the southern hemisphere westerlies. A reduction in richness during the last ∼1000 years is unlikely to be the result of precipitation change and may be related to more frequent burning of the landscape by hunter‐gatherers in an effort to increase availability of large prey.